Efficacy of Weight Reduction on Pediatric Nonalcoholic Fatty Liver Disease: Opportunities to Improve Treatment Outcomes Through Pharmacotherapy - Friesen, Chance S.; Hosey-Cojocari, Chelsea; Chan, Sherwin S.; Csanaky, Iván L.; Wagner, Jonathan B.; Sweeney, Brooke R.; Friesen, Alec; Fraser, Jason D.; Shakhnovich, Valentina (Frontiers in Endocrinology, 2021)
Obesity is the single greatest risk factor for nonalcoholic fatty liver disease (NAFLD). Without intervention, most pediatric patients with NAFLD continue to gain excessive weight, making early, effective weight loss intervention key for disease treatment and prevention of NAFLD progression. Unfortunately, outside of a closely monitored research setting, which is not representative of the real world, lifestyle modification success for weight loss in children is low. Bariatric surgery, though effective, is invasive and can worsen NAFLD postoperatively. Thus, there is an evolving and underutilized role for pharmacotherapy in children, both for weight reduction and NAFLD management. In this perspective article, we provide an overview of the efficacy of weight reduction on pediatric NAFLD treatment, discuss the pros and cons of currently approved pharmacotherapy options, as well as drugs commonly used off-label for weight reduction in children and adolescents. We also highlight gaps in, and opportunities for, streamlining obesity trials to include NAFLD assessment as a valuable, secondary, therapeutic outcome measure, which may aid drug repurposing. Finally, we describe the already available, and emerging, minimally-invasive biomarkers of NAFLD that could offer a safe and convenient alternative to liver biopsy in pediatric obesity and NAFLD trials.